2018
DOI: 10.1016/j.juro.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Immunonutrition Modulates Inflammatory Response after Radical Cystectomy: Results of a Pilot Randomized Controlled Clinical Trial

Abstract: Th1-to-Th2 ratios, peak interleukin-6 levels and plasma arginine suggest that consuming specialized immunonutrition counteracts the disrupted T-helper balance, lowers the inflammatory response and prevents arginine depletion due to radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 30 publications
0
72
0
1
Order By: Relevance
“…Both groups of patients received 5 days of their supplement before and after surgery. Patients receiving the arginine-containing supplement experienced a 39% reduction in late postoperative infections ( p = 0.027) [20••]. …”
Section: Preoperative Immunonutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both groups of patients received 5 days of their supplement before and after surgery. Patients receiving the arginine-containing supplement experienced a 39% reduction in late postoperative infections ( p = 0.027) [20••]. …”
Section: Preoperative Immunonutritionmentioning
confidence: 99%
“…In the patients that received the arginine-containing supplement, the balance of Th1-Th2 T cells was maintained at the time of surgery, and for those who received the non-arginine-containing supplement, it was not maintained (p = 0.027). In addition, the plasma concentration of IL-6 was significantly lower in patients receiving immunonutrition supplementation ( p = 0.020), suggesting that this intervention counteracts the disrupted Th1-Th2 balance and pro-inflammatory response after radical cystectomy [20••, 22••].…”
Section: Preoperative Immunonutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a meta‐analysis by Tyson and Chang, ERAS protocols have reduced lengths of stay, improved postoperative bowel function, and reduced some (low‐grade) complications, but they have not reduced readmission rates; this confirms the findings of many published single‐institution series around the world. On the heels of ERAS, an explosion of interventions to further reduce complications and prevent readmission have followed: identifying and reducing malnutrition, improving fitness through exercise, targeting mental health and anxiety, and comprehensive programs that target multiple domains (prehabilitation) . Unfortunately, each of these interventions (including ERAS) entail additional information and education on top of an overload of preoperative education that Smith et al have identified as overwhelming for patients.…”
mentioning
confidence: 99%
“…In a recent issue of the Journal of Urology , Hamilton-Reeves et al ( 1 ) reported interesting results of a prospective, randomized study that sought to compare the effects of a short-term specialized immunonutrition (SIM) with those of a standard oral nutrition supplement (ONS) on the acute inflammatory response and arginine status in patients with bladder cancer undergoing radical cystectomy (RC). RC involves several invasive procedures and is associated with high rates of complications and morbidity, partly due to extensive lymph node dissection and urinary diversions using intestinal segments, for example, orthotopic neobladders and ileal conduits.…”
mentioning
confidence: 99%